Mixed-Gas Selectivity Based on Pure Gas Permeation Measurements: An Approximate Model - Alexander O. Malakhov (MDPI AG, 2021)
An approximate model based on friction-coefficient formalism is developed to predict the mixed-gas permeability and selectivity of polymeric membranes. More specifically, the model is a modification of Kedem’s approach to flux coupling. The crucial assumption of the developed model is the division of the inverse local permeability of the mixture component into two terms: the inverse local permeability of the corresponding pure gas and the term proportional to the friction between penetrants. Analytical expressions for permeability and selectivity of polymeric membranes in mixed-gas conditions were obtained within the model. The input parameters for the model are ideal selectivity and solubility coefficients for pure gases. Calculations have shown that, depending on the input parameters and the value of the membrane Peclét number (the measure of coupling), there can be both a reduction and an enhancement of selectivity compared to the ideal selectivity. The deviation between real and ideal selectivity increases at higher Peclét numbers; in the limit of large Peclét numbers, the mixed-gas selectivity tends to the value of the ideal solubility selectivity. The model has been validated using literature data on mixed-gas separation of n-butane/methane and propylene/propane through polymeric membranes.